Identifying diverging sustainability meanings for water policy: A Q-method study in Phoenix, Arizona - Iribarnegaray, Martín Alejandro (2021)
We identify and describe social perspectives on the sustainability of the water sector in the metropolitan area of Phoenix, Arizona. Using Q methodology, we find evidence for different meanings of sustainability when stakeholders are presented with concrete policy options and applications in spite of an apparently widespread agreement on the concept of sustainability itself. We put the social perspectives articulated by local stakeholders in perspective by analyzing whether they adhere to a commonly used set of sustainability principles when applied to water management and governance. The analysis indicates that although there is some level of acceptance of sustainability principles among the social perspectives identified, there are important discrepancies in the salience of different principles. Results suggest that when people are interacting in policy-making processes they tend to support their previously held own vision of the problems and that their normative considerations may be opposed to broadly accepted sustainability discourses. The different visions of water sustainability may have a direct impact on the water policy-making process depending on the position and influence of the actors involved in the governance scheme.